Reassessing U.S.-Indonesia Development Cooperation: A Constructivist Analysis of the USAID Aid Suspension and Its Geopolitical Implications - Setiawan, Asep (Yayasan Ilomata, 2025)
The suspension of USAID funding to Indonesia in 2025, following a 90-day freeze on U.S. foreign aid, disrupted key development initiatives and reshaped the diplomatic landscape. This study examines the impact of the aid freeze on U.S.-Indonesia relations, using a constructivist approach to explore how shifting norms, identity changes, and evolving diplomatic narratives influence bilateral engagement. The research focuses on the effects of the aid suspension on critical sectors such as health, education, economic empowerment, and environmental sustainability, while also analyzing Indonesia's response to shifting geopolitical alignments. Through document analysis and literature review, the study investigates official reports, policy documents, and academic discourse on U.S. foreign aid and Indonesia’s strategic responses. Findings indicate that the suspension disrupted long-standing programs, particularly in healthcare and governance, leading to financial strain, program terminations, and a decline in trust toward U.S. commitments. Furthermore, Indonesia’s pivot toward alternative partnerships, particularly with China, highlights changing diplomatic dynamics. This study underscores that foreign aid is not just a financial transaction but a tool for norm-building, identity reinforcement, and geopolitical strategy. It emphasizes the importance of consistent aid policies to maintain credibility and trust. As Indonesia recalibrates its foreign policy, this research highlights broader implications for U.S. influence in Southeast Asia and the role of alternative global donors.